Rules of the Newfoundland Mutual Marine Insurance Club [electronic resource]. - Newfoundland Mutual Marine Insurance Club. ([St. John's, Nfld.? : s.n.], 1896)
Erratum--p. 25. "It is earnestly requested that all owners and masters having vessels . " Electronic reproduction. Mode of access: Internet. 44